2014
DOI: 10.3389/fmicb.2014.00378
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of DC subsets in MCMV infection to better understand immune protection against viral infections

Abstract: Infection of mice with murine cytomegalovirus (MCMV) recapitulates many physiopathological characteristics of human CMV infection and enables studying the interactions between a virus and its natural host. Dendritic cells (DC) are mononuclear phagocytes linking innate and adaptive immunity which are both necessary for MCMV control. DC are critical for the induction of cellular immunity because they are uniquely efficient for the activation of naïve T cells during their first encounter with a pathogen. DC are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 141 publications
(241 reference statements)
1
53
0
1
Order By: Relevance
“…Because macrophages, conventional dendritic cells (cDC), and plasmacytoid dendritic cells (pDC) have all been described to produce IL-12 in vivo during pathogen challenge (Alexandre et al, 2014; Trinchieri, 2003), we utilized Il-12p40 -YFP reporter mice to determine the major cellular source of local IL-12 in virally infected tissues. Unbiased analysis of total YFP + cells revealed that the majority of IL-12 producing cells at 12 hours PI in the PC and liver, or at 36 hours PI in the lung, respectively, were CD64 − CD11c hi MHCII hi CD11b − XCR1 + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because macrophages, conventional dendritic cells (cDC), and plasmacytoid dendritic cells (pDC) have all been described to produce IL-12 in vivo during pathogen challenge (Alexandre et al, 2014; Trinchieri, 2003), we utilized Il-12p40 -YFP reporter mice to determine the major cellular source of local IL-12 in virally infected tissues. Unbiased analysis of total YFP + cells revealed that the majority of IL-12 producing cells at 12 hours PI in the PC and liver, or at 36 hours PI in the lung, respectively, were CD64 − CD11c hi MHCII hi CD11b − XCR1 + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DC are heterogeneous mononuclear phagocytes which can be classified in different subsets due to their ontogeny, surface markers, and functions (24). Murine plasmacytoid DC (pDC) are described as CD11b Ϫ CD11c int SiglecH ϩ and are the major source of interferon alpha/beta (IFN-␣/␤) in response to MCMV infection (25)(26)(27).…”
mentioning
confidence: 99%
“…However, all of these studies were performed with monocultures of DC infected at a high multiplicity of infection (MOI), which might not reflect the in vivo situation, where most of the infected cells are epithelial and endothelial cells, which show higher permissiveness for MCMV than DC. Hence, it is still unclear if DC restrict or contribute to viral replication and spread (24).…”
mentioning
confidence: 99%
“…TLR‐dependent plasmacytoid dendritic cells (pDCs) are thought to be the primary cellular source of type 1 IFNs, although there are recent reports that the earliest type 1 IFN production following CMV is mediated by cGAS‐STING signaling in non‐hematopoietic cells, monocyte‐derived DCs, and macrophages . pDCs have also been described to produce IL‐12 during pathogen challenge . However, a recent study, using an unbiased analysis of YFP + cells from Il‐12p40 ‐YFP reporter mice, identified XCR1 + conventional dendritic cells (cDC1s) as the major early producers of IL‐12 in infected tissues following MCMV infection .…”
Section: Waves Of Antiviral Immunitymentioning
confidence: 99%